2020
DOI: 10.1111/hsc.13172
|View full text |Cite
|
Sign up to set email alerts
|

Communicating with older adults about sexual issues: How are these issues handled by physicians with and without training in human sexuality?

Abstract: Sexuality is an important part of health and emotional well-being throughout the entire life cycle, including during old age (American Association of Retired Persons, 2010;DeLamater, 2012;Kasif & Band-Winterstein, 2017). Nevertheless, despite its importance and despite the evident changes that take place in sexual functioning during this period, little is known about how physicians discuss or approach the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…It seems logical that the professionals with higher training in sexuality scored higher in the global score and the domains that defined the professional procedures on sexuality, family planning, and professional competence. However, contrary to several authors’ findings [ 6 , 12 , 40 , 41 , 42 ], we found no differences in the attitude of the professionals regarding their training in sexuality. We believe this is an exciting finding, as our interpretation is that if family physicians’ attitudes toward sexuality is the same, independently of their training in sexuality, it is because finally, professionals, whether trained in sexology or not, are at least beginning to be aware of the importance of adopting a proactive attitude to this issue.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It seems logical that the professionals with higher training in sexuality scored higher in the global score and the domains that defined the professional procedures on sexuality, family planning, and professional competence. However, contrary to several authors’ findings [ 6 , 12 , 40 , 41 , 42 ], we found no differences in the attitude of the professionals regarding their training in sexuality. We believe this is an exciting finding, as our interpretation is that if family physicians’ attitudes toward sexuality is the same, independently of their training in sexuality, it is because finally, professionals, whether trained in sexology or not, are at least beginning to be aware of the importance of adopting a proactive attitude to this issue.…”
Section: Discussioncontrasting
confidence: 99%
“…The level of training in sexual health among professionals is usually related to a more excellent approach to patients’ sexuality in their clinical practice, and understanding the development of this training is a priority to improve the skills of professionals [ 6 , 12 ]. The lack of training, consequently, conditions low confidence to address these issues, a poor perception of available therapeutic options and an underestimation of the prevalence of these difficulties, so they can be infra-diagnosed [ 12 ]. There is often an assumption that the sexual sphere passes into the background or that its deterioration is expected when other diseases appear [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different authors have demanded to reduce this problem by using well‐validated, standardized instruments (e.g., McCabe et al., 2016 ; Simons & Carey, 2001 ). In clinical care, many practitioners (e.g., psychotherapists and physicians) feel insecure and ill‐equipped to diagnose and treat sexual dysfunctions (Levkovich et al., 2021 ; Zannoni et al., 2021 ). A valid, reliable, and easily applicable structured diagnostic instrument for sexual dysfunctions would help to reduce uncertainties in clinical care and enhance diagnostic validity in clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GPs with sexual medicine training are more likely to talk openly with their patients about sexuality than GPs without training. 3,6 Previous studies show that GPs prefer an open conversation about patient's sexual history rather than a structured approach (eg, according to ICD-10). 3,7 Younger GPs addressed sexual problems in practice more often by themselves than their older colleagues.…”
Section: Introductionmentioning
confidence: 99%